2019
DOI: 10.3390/su11102976
|View full text |Cite
|
Sign up to set email alerts
|

Green Transportation and Logistics Performance: An Improved Composite Index

Abstract: This article constructs an environmental logistics performance index (ELPI) for assessing the overall performance in green transportation and logistics practices of 112 countries. The index is measured by logistics performance index (LPI), CO2 emissions and oil consumption from the transport sector, using a range-adjusted measure (RAM) of the data envelopment analysis (DEA). ELPI effectively reflects the tradeoff between logistics efficiency and environmental protection in transportation. This article analyzes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 47 publications
7
48
0
Order By: Relevance
“…Recent study, concluded that for logistics index performance is to be measured by CO2 (Carbon Dioxide) emissions and fuel consumption from the transport used using range adjusted measure (RAM) from the data envelopment analysis (DEA). This area alone are contributing to 42% of transport related CO2 emissions in the world in 2018 [14].The result of the study showed that the country with high income is better in preserving the environment compared to the country with lower income. The result also favor the wealth continent especially in Western Europe.…”
Section: Green Initiatives and Implementationmentioning
confidence: 93%
“…Recent study, concluded that for logistics index performance is to be measured by CO2 (Carbon Dioxide) emissions and fuel consumption from the transport used using range adjusted measure (RAM) from the data envelopment analysis (DEA). This area alone are contributing to 42% of transport related CO2 emissions in the world in 2018 [14].The result of the study showed that the country with high income is better in preserving the environment compared to the country with lower income. The result also favor the wealth continent especially in Western Europe.…”
Section: Green Initiatives and Implementationmentioning
confidence: 93%
“…Focusing on the industrial environment, Le et al [9] argues that sustainability has become an important factor in competitive advantage for companies. Increasingly, society requires industries to develop sustainable practices throughout their manufacturing, supply and distribution operations [10,11]. Bask et al, Björklund and Forslund [12,13] corroborate this point of view which reinforces the need to better understand the role of sustainability in the development of logistics activities.…”
Section: Introductionmentioning
confidence: 89%
“…Herold and Lee [64] investigated the carbon reports disclosed by some giant international logistics enterprises, e.g., UPS, FedX and DHL, and compared their sustainability-related strategies, namely legitimacy-seeking arguments versus energy and emission reduction. In addition, a variety of qualitative analysis measures, such as fuzzy multi-criteria evaluation modeling [65], data envelopment analysis [66], and analytic hierarchy processes [67] were also widely applied to illuminate the logic between SEE performance and G&SL.…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%